Kangerlussuaq: evolution and maturation of a cultural landscape in Greenland - Dzik Anthony J. (Bulletin of Geography. Socio-Economic Series)
The cultural landscape reflects the composite influences of the regional physical, cultural, and technological environments. It is a dynamic entity which evolves over time and the perceptions of its human inhabitants is influential in the process. This paper is a descriptive analysis of Kangerlussuaq, a young but maturing settlement located in west Greenland near the inland ice. The site’s natural resource base did not attract permanent settlement by the Inuit or Scandinavian colonists, but in the early days of the World War II, the American military took advantage of the exceptional flying conditions here and established an air base. In time, civilian functions developed as Kangerlussuaq became the hub for air travel in Greenland. A transitory utilitarian settlement was eventually transformed into a more permanent settlement. In recent years there seems to be a growing sense of community and place attachment as the cultural landscape begins to exhibit more of the components of a real ‘town’.